2015
DOI: 10.1007/s10620-015-3937-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Clinical Role of Cdc5L as a Novel Cell Cycle Protein in Hepatocellular Carcinoma

Abstract: Our findings suggested that Cdc5L could play an important role in the tumorigenesis of HCC and thus be a potential therapeutical target to prevent HCC progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Cell division cycle 5-like (CDC5L) is a cell cycle regulatory element of G2/M transformation and is involved in the catalytic steps of mRNA splicing and DNA damage repair. Studies indicated that CDC5L expression in glioma and hepatocellular carcinoma was increased, and CDC5L interference could increase the cell cycle arrest in G2 phase and inhibit the proliferation of glioma cells and hepatoma cells [15,16]. However, CDC5L has not been studied in MM.…”
Section: Introductionmentioning
confidence: 99%
“…Cell division cycle 5-like (CDC5L) is a cell cycle regulatory element of G2/M transformation and is involved in the catalytic steps of mRNA splicing and DNA damage repair. Studies indicated that CDC5L expression in glioma and hepatocellular carcinoma was increased, and CDC5L interference could increase the cell cycle arrest in G2 phase and inhibit the proliferation of glioma cells and hepatoma cells [15,16]. However, CDC5L has not been studied in MM.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Cdc5L in mammalian cells causes shorter G2 phase and reduced cell size [16] and knockdown of Cdc5L results in dramatic mitotic arrest [17] and chromosome misalignments [18]. Recently, both Prp19 and Cdc5L have been characterized to be overexpressed in HCC tissues and their overexpression are positively correlated with poor prognosis [17,19]. Considering the importance of Prp19 and Cdc5L within this complex, the relationship between them deserves to be investigated in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…High expression of CDC5L was an independent prognostic factor for poor survival of HCC patients. In vitro studies showed that overexpression of CDC5L contributed to cell cycle progress of HCC cells, while down-regulation of CDC5L resulted in cell cycle arrest at G2/M phase and reduced cell proliferation of HCC cells [26]. Moreover, higher phosphorylation of CDC5L was found in HCC cell line, MHCC97-H (high metastasis), indicating that it may participate in the metastasis of HCC [27].…”
Section: Discussionmentioning
confidence: 98%